Síntese, caracterização e estudos de citotoxicidade e alvo biológico de complexos quadráticos planos contendo Tiossemicarbazonas - Silva, Ludimila Thayane Paes (2019)
The diversity of cancer diseases and the side effects caused by the drugs commonly used in cancer treatment require different antineoplasic agents able to operate more specific and in a way to minimize the side effects. With that in mind, efforts are made to develop compounds for selective biological target, such as the enzime topoisomeraseIIα, or TOPOIIα, which has been widely studied. In a recent work of our research group, it was found that Pd(II) complexes with thiosemicarbazone ligand (N, S donor) and co-ligands’ phosphinic and halides, in a distorted square planar molecular geometry, showed cytotoxic activity against breast and lung tumor cell lines; they also inhibited TOPOIIα enzime at a 2,8 times smaller concentration than the standard drug, etoposide. This activity was atributed to the interaction of the complexed thiosemicarbazone ligand with enzime’s active sites. Therefore, in the present work, it was attempt to comprehend the importance of the co-ligands and of the thiosemicarbazone identity, as well as the metallic ion influence in the biological activities. Thereunto, in this work, changes in the molecular framework were performed: (i) substitution of co-ligands for another thiosemicarbazone molecule; (ii) changes in the thiosemicarbazone structure; (iii) metal ion identity. It was synthesized six thiosemicarbazones ligands (L) (N, S donor), thirteen new bischelate complexes structures in a square planar geometry : twelve Pd(II), divided in two analogues series of general formulae [Pd(L)2] and [Pd(HL)2]Cl2, differenciated by anionic and neutral ligands coordination, respectively, and a Ni(II) complex, [Ni(L)2]. After obtaining all the compounds (caracterized by spectroscopic and spectrometric thecniques), the investigation of cytotoxic activity of ligands and their Pd(II) complexes against the tumoral cell lines MCF-7 (breast) and DU-145 (prostate) and non-tumoral PNT2 (prostate) showed that the free thiosemicarbazone ligands presented low cytotoxicity (IC50> 50 μmol.L-1), while their Pd(II) complexes containing the lower molecular masses thiosemicarbazone presented IC50 values in the 12,00-0,22 μmol.L-1 interval for tumoral cell lines. It was not observed selectivity among the cell lines tested (tumoral and non-tumoral). Comparing the cytotoxicity exhibited by a Pd(II) complex containing the co-ligands, [PdCl(BT-M)(P(4FPh)3] (IC50 = 0,56 ± 0,1 μmol.L-1), and its bischelate anologues complexes of Pd(II) and Ni(II), [Pd(BT-M)2] (IC50 = 0,43 ± 0,3 μmol.L-1) and [Ni(BT-M)2] (IC50> 12μmol.L-1), against tumoral breast cancer cell line MDA-MD-231, it is suggested that metal ion identity is essencial in the cytotoxicity of complexes. Molecular Docking studies showed that the Pd(II) bischelate complexes do not present affinity with TOPOIIα active sites. Experimentally, it was observed that the most cytotoxic complexes of Pd(II) and the Ni(II) complex do not Interact significantly with DNA and they are not able to inhibit TOPOIIα (at concentrations of 1, 10 e 50 μmol.L-1), pointing out that these are not the biological targets of the complexes. It is suggested that, the absence of co-ligands could be the responsible for the loss of enzimatic inhibitory activity.